2015
DOI: 10.3390/ijerph120809282
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide Nanoparticle Penetration into the Skin and Effects on HaCaT Cells

Abstract: Titanium dioxide nanoparticles (TiO2NPs) suspensions (concentration 1.0 g/L) in synthetic sweat solution were applied on Franz cells for 24 h using intact and needle-abraded human skin. Titanium content into skin and receiving phases was determined. Cytotoxicity (MTT, AlamarBlue® and propidium iodide, PI, uptake assays) was evaluated on HaCat keratinocytes after 24 h, 48 h, and seven days of exposure. After 24 h of exposure, no titanium was detectable in receiving solutions for both intact and damaged skin. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(64 citation statements)
references
References 50 publications
3
59
0
2
Order By: Relevance
“…The results obtained were similar to the previous work done on three mammalian cells with 11 metal oxides using MTT assay [19]. They concluded that TNP 18.39 nm and ZNP 21.68 nm were produced cytotoxicity, cell viability reduction 50 % and induced membrane damage at concentrations greater than10 µg/ml of the exposure time 48 h [20,21].…”
Section: Discussionsupporting
confidence: 87%
“…The results obtained were similar to the previous work done on three mammalian cells with 11 metal oxides using MTT assay [19]. They concluded that TNP 18.39 nm and ZNP 21.68 nm were produced cytotoxicity, cell viability reduction 50 % and induced membrane damage at concentrations greater than10 µg/ml of the exposure time 48 h [20,21].…”
Section: Discussionsupporting
confidence: 87%
“…28 However, most researchers believe that TiO 2 NPs from sunscreens did not pose a significant health threat because they do not appear to significantly penetrate the skin. 29,30 Some studies have demonstrated in vitro cytotoxicity and genotoxicity of TiO 2 NPs in various cell lines, plants, and brains of mice after oral administration. 3133 Bioaccumulation, subacute toxicity, and tissue distribution of TiO 2 NPs was exhibited in goldfish ( Carassius auratus ) and C57BL/6 mice.…”
Section: Nanomaterials In Daily Life and Their Toxicitymentioning
confidence: 99%
“…The study by Xie et al ., performed in rats, showed that nano‐TiO 2 did not penetrate the stratum corneum in skin either intact or slightly damaged with 2% sodium lauryl sulphate (SLS) solution, both in vitro and in vivo . Moreover, in the study by Crosera et al ., performed on human skin in vitro by using static diffusion cells, nano‐TiO 2 was only detected in the epidermis of both healthy and needle‐abraded skin samples after a 24‐h exposure to a sonicated suspension of nano‐TiO 2 (606 μg/cm²; Table ). Of note, in that study, the total amount of nano‐TiO 2 was similar in both healthy and needle‐abraded skin, indicating that lesions did not increase permeation.…”
Section: Absorption and Distributionmentioning
confidence: 98%